Design and characterization of flat lens antenna using aperture-coupled microstrip patches - Ali Awaleh, Abdisamad (2015)
A planar discrete lens antenna is a low profile, light weight and cost effective solution to conventional and curved dielectric lenses. The basic theory of operation of flat lens antenna unit cell is to collimate the feed spherical electromagnetic incident wave into planar wavefront at the back of the aperture. Therefore, the array unit cell must be designed to establish the required phase adjustment. Flat lens antenna elements which are based on aperture-coupled microstrip patches are presented. The lens contains 7×7 elements with a diameter of 71 mm and operates in the X-band frequency range. The lens was experimentally validated and good agreement between simulation and measurement results were obtained. The achieved measured peak gain is 15.85 dB. This gives 6 dB gain enhancement for the system. The antenna 1-dB gain bandwidth and power efficiency are 7.8% and 58% respectively. A very good transmission phase shift of 340° is achieved with transmission coefficient of better than 2.25 dB. In addition, the measured radiation pattern results show that the antenna system has good symmetry between E and H plane with a half-power beamwidth of 16.2° and 16.6° in E-plane and H-plane respectively. Moreover, the proposed lens element employs a simple and less fabrication complexity mechanism for phase shift correction. Finally, the obtained results show that the proposed flat lens antenna is an attractive choice for the applications of wireless airborne systems such as VSAT (Very Small Aperture Terminal).